Public awareness of benefits of Gingko biloba in memory dysfunction and choice of brands among pharmacists in Alor Star, Kedah & Kuantan, Pahang - Ali, Fathilah; Kyi, Kyi Tha (2010)
Aging causes a regression of physiological function. Complaints of declining memory are common with advancing age. Gingko extracted from leaves of Gingko biloba (maidenhair tree) has neuroprotective properties against memory dysfunction and neuronal death in Alzheimer's disease. The objective of this study was to determine the public awareness of benefits of Gingko biloba in memory dysfunction and choice of brands among pharmacists in retail pharmacies located around Alor Star, Kedah & Kuantan, Pahang. A randomized cross sectional study with the participants of customers age 40 years and above was conducted in 25 retail pharmacies in Alor Star, Kedah and 16 pharmacies in Kuantan, Pahang. The data was obtained through face to face interview guided by structured questionnaire. Only 23 out of 168 participants were the users of Gingko biloba while remaining 80.95% did not take any supplements to improve memory. Gingko biloba was widely used by elderly people, age range of 61-70 years old, for adjunctive therapy and 62.5% of user were Chinese, 20.12% were Malays and 9.38% were Indians. 71.87% of them were recommended by their doctors or pharmacists. The entire 32 users were satisfied with the product whereby 20 users have consumed it more than a year. The longest duration of taking Gingko biloba products was 8 years while the shortest duration was 3 weeks. 31.25% of them used the product to improve memory. The awareness of existence of Gingko product was 64% but awareness of benefits in memory dysfunction was still low (38%). 35% of respondents believed that they did not need the supplements where as 28% quoted that the supplements were expensive. Tebonin forte film coated tablet which was the pioneer of the product was the most trusted brand among the pharmacists. Reason of pharmacists choosing the certain brand were reliability (46.34%), customer's demand (24.34%) and promotion by supplier (29.27%). The stock turn over the product was 49% of pharmacies reorder their stock between 4 to 6 months. In conclusion, Gingko biloba was a supplement known to improve memory but the benefits was yet to be known by the public. The pharmacists chose certain types of brand was due to the reliability and also wanted to acknowledge and introduce the supplements that could help to boost and improve health.